Regulation of 1-MCP Pre-treatment on Refrigeration Quality of Kiwifruit under Vibration Stress - Yiyang LI; Haiying YANG; Guangting DENG; Yuying SUN; Shenghua DING; Rongrong WANG (Shipin gongye ke-ji)
Vibration stress is one of the main causes of postharvest loss of kiwifruit. In this study, the effects of vibration stress on the quality of kiwifruit during refrigeration (temperature 4±0.5 ℃, relative humidity 90%~95%, refrigeration time 40 d) were analyzed by performing three-dimensional vibration (frequency 5 Hz, amplitude 5 mm, vibration time 12 h) in the three directions of up and down, left and right, front and back of 'Hongyang' kiwifruit to simulate long-term transportation of asphalt pavement. Further, the regulation of 1-methylcyclopropene (1-MCP) pre-treatment on vibration stress was investigated. The results showed that vibration stress could accelerate the water loss, wrinkling and softening of kiwifruit during refrigeration. Compared with the control group, the peak value of respiration in the vibration group increased by 42.4% up to 110.01 mg/(kg·h), weight loss rate increased by 6.7%~14.4%, the contents of malondialdehyde and soluble solid increased respectively by 7.1%~28.8% and 6.5%~12.6%, the change in color was obvious and the value of ∆E increased by 9.3%~17.2%, and the cell wall structure was severely damaged during refrigeration. However, 1-MCP pre-treatment before vibration could effectively reduce the metabolic levels, its respiratory peak decreased to 62.35% of the vibration group and was only 68.59 mg/(kg·h). Meanwhile, the colloidal layer in the fruit cell wall was not degraded and more cytoplasmic contents were retained in 1-MCP+vibration group than that of vibration group, the original structure of the cell wall was better maintained. The increase of malondialdehyde and soluble solids content and the decrease of ascorbic acid content were delayed in 1-MCP+vibration group during refrigeration, and the activities of ascorbate peroxidase and catalase in the late stage of refrigeration were retained. The cluster analysis further verified that the fruit quality of vibration group was significantly different from that of other groups in the same period. The fruit quality of 1-MCP+vibration group was close to that of control group, which could alleviate the quality deterioration of kiwifruit caused by vibration stress. This study can provide a theoretical basis for kiwifruit preservation by logistics transportation and regulation of fruit quality deterioration caused by mechanical damage after harvest.